2003
DOI: 10.1021/cm0210492
|View full text |Cite
|
Sign up to set email alerts
|

Redox Behavior of Nanostructured Molybdenum Oxide−Mesoporous Silica Hybrid Materials

Abstract: Encapsulation of molybdenum oxide MoO 3 into ordered mesoporous silica materials is demonstrated using different synthetic routes. Either supramolecular polyoxometalates of the "Mü ller type" or Na 2 MoO 4 were used as precursors. Molybdenum oxide (MoO 3 )-silica hybrid materials were characterized using nitrogen-sorption experiments, transmission electron microscopy, small-angle X-ray scattering, and infrared spectroscopy. Under reducing conditions, the hybrid materials undergo an electrochromic transition fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Reduced diffusion not only makes the reaction slower, it can also change the reaction order. To study the influence of CRFs on kinetics experimentally, we used mesoporous silica materials possessing different pore sizes and loaded them with molybdenum trioxide (MoO 3 ) 93. The reduction of the MoO 3 was achieved by the infiltration of an aqueous solution of hydrazinium sulfate.…”
Section: Influence On Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced diffusion not only makes the reaction slower, it can also change the reaction order. To study the influence of CRFs on kinetics experimentally, we used mesoporous silica materials possessing different pore sizes and loaded them with molybdenum trioxide (MoO 3 ) 93. The reduction of the MoO 3 was achieved by the infiltration of an aqueous solution of hydrazinium sulfate.…”
Section: Influence On Kineticsmentioning
confidence: 99%
“… Kinetic plots for the reduction of MoO 3 ‐confined mesoporous silica materials with different pore sizes ( D p ≈2 nm (triangles), D p ≈5 nm (squares)) 93…”
Section: Influence On Kineticsmentioning
confidence: 99%
“…By embedding the catalytically active component into a well-defined superstructure (e.g., a hierarchically structured mesoporous matrix), it should be possible to simultaneously simplify and miniaturize the supported catalyst [14][15][16][17][18][19][20] and to utilize in the preparation the favorable effects of the spatially confined reaction conditions on the chemistry occurring in the porous solid [21]. However, this approach carries the risk of interference by the pore walls of the matrix.…”
Section: Introductionmentioning
confidence: 99%
“…A recent review [8] has poignantly highlighted the importance of micro-and nanostructured MoO 3 and related substoichiometric molybdenum oxides for charge storage/intercalation and particularly for electrochromics, which has been studied for a wide range of disordered partially crystalline or polycrystalline materials including amorphous MoO 3 films. Only brief studies of nanocrystalline MoO 3 materials for electrochromic applications have been reported to date [9] limited by the availability of single crystal MoO 3 synthesis with size and crystal structure control and suitable surface deposition methodologies.…”
Section: Introductionmentioning
confidence: 99%